1995
DOI: 10.1002/ajmg.1320570222
|View full text |Cite
|
Sign up to set email alerts
|

Free radicals, anticonvulsants, and the neuronal ceroid‐lipofuscinoses

Abstract: The relationship between free radicals and scavenger enzymes, and the disorders called the neuronal ceroid-lipofuscinoses, has long been an argumentative one. Recent evidence would seem to support the fact that such a relationship might exist but that it is indirect. The relationship does not seem due to an inborn error of free radical scavenger enzyme metabolism. Anticonvulsants play a role, as they influence free radical generating systems. At this juncture, no one has studied the relationship of anticonvuls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 12 publications
2
55
0
Order By: Relevance
“…Many studies suggest that membrane lipid peroxidation may be causally involved in some forms of epilepsies, and the decrease in free radical scavenging enzyme activity is believed to cause the increased risk of seizure recurrence (4,12,63) and idiosyncratic drug reaction encountered in the management of epilepsy (55,63,64). In addition, Many conventional AEDs are metabolized to generate reactive metabolites with capability of covalent binding to macromolecules (65).…”
Section: +mentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies suggest that membrane lipid peroxidation may be causally involved in some forms of epilepsies, and the decrease in free radical scavenging enzyme activity is believed to cause the increased risk of seizure recurrence (4,12,63) and idiosyncratic drug reaction encountered in the management of epilepsy (55,63,64). In addition, Many conventional AEDs are metabolized to generate reactive metabolites with capability of covalent binding to macromolecules (65).…”
Section: +mentioning
confidence: 99%
“…It has been reported that increased generation of free radicals or reduced activity of antioxidative defense mechanisms can cause some forms of seizures and in addition, increases the risk of seizure recurrence (4,5). Many antiepileptic drugs (AEDs) are metabolized to generate reactive metabolites with the capability of covalent binding to macromolecules as proteins or other vital biomolecules and hence eliciting systemic toxicity (5 -7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Superoxide scavenging activity of the compounds was determined by McCord and Fridovich method [24], which depends on light induced superoxide generation by riboflavin and corresponding reduction of NBT [25][26][27]. The assay mixture contained EDTA (Ethylenediamine tetra-acetic acid) solution (6.6 mM) containing NaCN (3 µg), riboflavin (2 µM), NBT (50 µM), test substances and phosphate buffer (67 mM, pH = 7.8) in a final volume of 3 mL.…”
Section: Nbt-riboflavin Photo Reduction Methodsmentioning
confidence: 99%
“…Long-term use of antiepileptic drugs has been shown to increase free radical formation and cause oxidative damage within neuronal cells (Maertens et al, 1995). The metabolism of valproate may trigger oxygen dependent tissue injury and elevate the free radicals in the body (Cengiz et al, 2000).…”
Section: Introductionmentioning
confidence: 99%